Gothic television - Wheatley, Helen (Helen M.) (Manchester Gothic (Manchester, England)., 2017)
Analysing key programmes - from 'Mystery and Imagination' and 'Dark Shadows' to 'The Woman in White' and 'Twin Peaks' - this text looks at the appearance of the gothic on television, uncovering an aspect of TV drama history which has remained critically unexplored.